Analysis of Financial Performance of Asian Paints Ltd. (From 2008-09 to 2012-13): A Case Study of Asian Paints Ltd. (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Efficient management offinance is very important for the success of an enterprise. Term financialperformance is very dynamic term. The subject matter of financial performancehas been changing very rapidly. In present time greater importance is given tofinancial performance. So, here an attempt is made by me to analysis thefinancial performance of the selected unit i.e. Asian Paint Ltd. While analyzing thefinancial performance of the selected units, we include the analysis of workingcapital and analysis of profitability.